2020
DOI: 10.1001/jamanetworkopen.2020.24583
|View full text |Cite
|
Sign up to set email alerts
|

Association of Racial/Ethnic and Gender Concordance Between Patients and Physicians With Patient Experience Ratings

Abstract: IMPORTANCEThe Press Ganey Outpatient Medical Practice Survey is used to measure the patient experience. An understanding of the patient-and physician-related determinants of the patient experience may help identify opportunities to improve health care delivery and physician ratings. OBJECTIVETo evaluate the associations between the patient experience as measured by scores on the Press Ganey survey and patient-physician racial/ethnic and gender concordance. DESIGN, SETTING, AND PARTICIPANTS A cross-sectional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
266
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(271 citation statements)
references
References 38 publications
5
266
0
Order By: Relevance
“…Acceptability is influenced by both racial/ethnic minority populations’ expectations of, and reality with, experiencing discrimination in healthcare systems and their mistrust of healthcare providers as a result of historical unethical and criminal behaviors, such as unauthorized treatments and experiments performed on Black people, and present-day biases (e.g., pain perception) [ 64 , 65 , 66 ]. Acceptability may be facilitated by racial–ethnic concordance between patients and providers [ 67 ]. However, the closure of many Black medical schools in the 20th century may have reduced the number of Black physicians by ~35,000 roughly over the last century.…”
Section: Social Determinants Of Health and Their Role In Rural Andmentioning
confidence: 99%
“…Acceptability is influenced by both racial/ethnic minority populations’ expectations of, and reality with, experiencing discrimination in healthcare systems and their mistrust of healthcare providers as a result of historical unethical and criminal behaviors, such as unauthorized treatments and experiments performed on Black people, and present-day biases (e.g., pain perception) [ 64 , 65 , 66 ]. Acceptability may be facilitated by racial–ethnic concordance between patients and providers [ 67 ]. However, the closure of many Black medical schools in the 20th century may have reduced the number of Black physicians by ~35,000 roughly over the last century.…”
Section: Social Determinants Of Health and Their Role In Rural Andmentioning
confidence: 99%
“…5 As a diverse workforce is more likely to provide care for underserved populations and foster higher levels of trust, efforts to recruit and retain underrepresented individuals from racial/ethnic minority groups, such as Black, Hispanic, Native American or Alaskan Native, Native Hawaiian or Pacific Islander individuals, within OBGYN are critical as we strive to close gaps in health disparities. 2 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…1 While addressing these disparities requires multiple strategies, one approach is to increase diversity among health care practitioners, as patient-physician racial/ethnic concordance is associated with increased patient satisfaction and higher levels of trust. 2 Previous research, such as a 2020 study by Nieblas-Bedolla et al, 3 indicates that the OBGYN workforce includes more underrepresented physicians compared with other specialties. By examining current and recent trainees, we can assess recruitment efforts and estimate the future racial and ethnic diversity of the physician workforce.…”
Section: Introductionmentioning
confidence: 98%
“…Despite their widespread use, multiple studies have reported that Press-Ganey scores can be negatively influenced by factors such as ED wait time, being treated in a "fast-track" area, or even the race and gender of the clinician. 4…”
Section: Press-ganey: Friend or Foe?mentioning
confidence: 99%